Elaboración del marco teórico sobre la gestión sistémica organizacional (2018)
In this research project seeks to establish the importance of organizational systemic management understanding its scope within each of the companies to achieve high performance. It is necessary to cover theoretical contents of different authors having several technical perspectives to obtain a planning, execution and evaluation of all the processes of the organizations that allow an optimization of the systems and resources. This project is developed through the collection of information in the different information bases.